History of Sustainability Reporting - Lucky Ogbomo Osagioduwa; A. O. Enofe; F. P. Izedonmi; E. L Dabor; Elizabeth N. Atube (ESUT JOURNAL OF SOCIAL SCIENCES, 2023)
In the late 20th century, as global attention turned towards the environmental and social impacts of business activities, the history of sustainability reporting began to unfold, including Africa's involvement. During the 1970s and 1980s, there was a growing recognition of the importance for businesses to prioritize their environmental and social responsible particularly as extractive activities grew particularly in Nigeria, Ghana, and Togo.  This study employed the historical-comparative research design to view the historic exodus of sustainability reporting in these three nations. In this sense, the cardinal objective of this paper is to highlight chronologically the historical development of sustainability reporting starting from 1957 for Ghana while 1960 for Nigeria and Togo to 2021. Sustainability policies and initiatives formed during this period in the three countries were also examined. Nigeria’s history was divided into four eras being that Nigeria has initiated various relevant policies and programs. This is one of the rare studies that have conducted a comparative historic examination of sustainability reporting employing independence base historic progression. The study concludes that while several efforts had been geared towards the advancement of sustainability reporting among the three nations, evidence indicates that sustainability reporting in 2023 was signed into law in Nigeria. The study, therefore, recommends that Ghana and Togo should strive towards legalizing sustainability reporting in their financial reporting framework.